Possible levels of integration of the Internet network in Secondary Education (Journal of Parents and Teachers, 2014)
ICTs are increasingly present in our daily lives and that is why they are gradually starting to integrate into the classrooms of schools. However, there is still a long way to go in order to achieve full and adequate integration of new technologies in educational settings. This article explains the different levels of ICT integration.
Keywords: ICT; ICT integration; use of ICT; educational environment; integration phases.